การออกแบบชั้นรองพื้นทางของถนนชนบทโดยใช้วัสดุท้องถิ่นบริเวณภาคตะวันออกของประเทศไทย - วรากร กริ่มวงษ์รัตน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
The purpose of this study was to determine the values of Resilient Modulus (Mr) of local lateritic soil. The properties of the study soil were below the standard for the high-type highway material but it was suitable for local roads subbase use. The research developed the design charts for subbase of low to medium traffic volume flexible pavement using the KEN LAYER program. Materials understudied were lateritic soil: A-1-a, A-2-4 and A-2-6 from 3 eastern provinces of Thailand, namely-Chonburi, Chachoengsao and Prachinburi. The soils from the three sites met the specification of plasticity but failed to meet the gradation standard for use as a subbase course so they can be used for the road construction by analytical design. Nonetheless, the Mrs were experimented by AASHTO T292-91 protocal and then used to develop the design chart suitable for these material properties. The result was found that the average values of Mr for type: A-1-a, A-2-4 and A-2-6 were 4020 0.36 MPa, 4450 0.26 MPa and 4670 0.25 MPa respectively. The effect of moisture on Mr and design values was also investigated. There were little effect on Mr.